Le tournant environnemental en Amazonie : ampleur et limites du découplage entre production et déforestation - François Laurent; Damien Arvor; Marion Daugeard; Reinis Osis; Isabelle Tritsch; Emilie Coudel; Marie-Gabrielle Piketty; Marc Piraux; Cecilia Viana; Vincent Dubreuil; Ali F. Hasan; François Messner (EchoGéo)
The Amazon has recently experienced a dramatic decline in deforestation coupled with economic development. However, this process is uneven. While large and medium-sized producers are intensifying and diversifying their production systems in the already cleared areas, thus apparently abandoning expansion strategies at the moment, family farming remains aloof from this decoupling between production and deforestation. In this article, the commitments of public authorities and sectors, their effects on deforestation and inequalities of adaptation are analyzed at the scale of the Legal Amazon and in a municipality considered as a model because involved in a Município Verde initiative: Paragominas, in the Eastern Amazon.